Studi korelatif Pendidikan Orang Tua Berhubungan Dengan Usia Gestasi Bayi Lahir Prematur - Herlina Herlina (AKPER Pasar Rebo, 2020)
Indonesia is a country that has the fifth highest preterm birth rate in the world in 2018. One of the causes of premature infant is the socioeconomic condition of the family. One of the factors that determines the level of family socio-economic is the education of parents. This study aims to analyze the relationship between parental education and gestational age of infant whose born prematurly. This research uses descriptive research method with cross sectional approach on 267 prematur infants obtained using total sampling technique. The results showed that most of the education of fathers and mothers was Senior High School (SLTA). The results of the statistical analysis of paired t test showed that there was a relationship between parental education and gestational age of the infant whosed born prematurly (p <0.001, 95% CI). Based on the results of the study, the researchers suggest that reproductive health education is given at the senior secondary level as an effort to prevent prematur infants.